A Study of the Effect of Grouting with Cement Kiln Dust (CKD) on Coastal Sandy Soil Strength to Unconfined Compression - فياض توفيق; العبده رامي; السقر فاتن (Latakia University Journal -Engineering Sciences Series, 2021)
Grouting technology is one of the latest techniques used to improve foundation soils, is classified in several types, the type of soil to be treated; is considered the most important factor in the choice of grouting type. Permeation Grouting is commonly used to improve the engineering properties of granular soils, the grouting material is pumped liquidly into the foundation soil under pressure, penetrating into the soil voids and then hardening and forming a material bonding the granules of the soil, improving the properties of the grouted soil without disturbing its natural structure, which is the type used in this research The research aims to study the effect of (CKD) permeation grouting on the unconfined compressive strength (UCS) of sandy soil in the coastal region, to achieve that a laboratory grouting model that simulates grouting on-site process has been designed and fabricated. The soil samples were grouted with a suspension consisting of different percentages of cement kiln dust (2,4,6,8,10,12)% as a ratio of dry weight of the treated soil, and different mixing ratios (Water:CKD) (W:C=2:1, 4:1,6:1,8:1,10:1), then we conducted unconfined compressive test on the grouted samples, for (7&28) days curing. The results demonstrate that the grouted sand has gained high unconfined compressive strength, where the values of unconfined compressive strength and initial tangent young’s modulus of grouted soil increased with increasing the (CKD) percentage and curing period, while decreased by increasing in the (W:CKD) ratio of grouting suspension, as well the value of increased with increasing the and the relation between them is a linear.